Intraoperative ultrasound in neurosurgical procedures - V A Kiran Kumar; N A Sai Kiran; B Girija Kumari; Ranabir Pal; V Umamaheswar Reddy; Amit Agrawal (Apollo Medicine)
Introduction: The objective of the present study was to study the utility and the effectiveness of intraoperative ultrasound in neurosurgical procedures and to assess the outcome. Material and Methods: In this prospective study, operative procedures by a single surgeon under intraoperative ultrasound localization for basal ganglia/thalamic haematoma or traumatic brain contusions or brain tumours were included. Ultrasound scanning of the brain was performed before and after the excision of the lesion and during the procedure to verify the extent of removal of the lesion. Results: 74 patients underwent surgery for brain tumor/basal ganglia bleed/head injury with hemorrhagic contusion with the help of intraoperative ultrasound. Gross tumor resection was noted in 25 out of 36 cases of brain tumors (69.44%), complete evacuation of hematoma was noted in 14 out of 34 cases(41.2%) of basal ganglia bleed and in 2 out of 4 cases (50%) of intracerebral contusion. As per Modified Rankin scale (MRS)score, among the brain tumor cases, all patients had fared well in recovery and had better MRS scores except in one patient who expired during postoperative period. Conclusions: IoUS is a widely accessible, cheap, portable and less space occupying and reliable imaging tool to follow and modify the surgical plan in real time, and is more accurate and helpful in complete tumor resection, evacuation of intracerebral bleeds and contusions, and biopsy of deep seated lesions. It is easy and safe to handle with no risk of radiation.